Socioeconomic status, hair cortisol and internalizing symptoms in parents and children. (April 2017) - Ursache, Alexandra; Merz, Emily C.; Melvin, Samantha; Meyer, Jerrold; Noble, Kimberly G.
Highlights: Parents with lower family incomes had higher hair cortisol concentration (HCC). Relation between HCC and income was strongest among the most disadvantaged parents. Lower parental education was associated with higher HCC in parents and children. Perceived stress mediated socioeconomic disparities in parents' anxiety symptoms. HCC marginally mediated socioeconomic disparities in parents' anxiety symptoms. Abstract: Socioeconomic disadvantage is consistently linked with higher risk for internalizing problems, and stress is likely one important mechanism explaining this increased risk. Few studies have examined socioeconomic differences in hair cortisol, a novel biomarker of long-term adrenocortical activity and chronic stress. Moreover, no studies have examined whether differences in hair cortisol might explain socioeconomic disparities in internalizing problems. To address these gaps, we first examined relations of socioeconomic status (SES; family income and parental education) to variation in both parents' and children's hair cortisol concentrations (HCC) and then tested whether HCC and perceptions of stress mediated relations of SES to parents' and children's internalizing symptoms. Participants were a socioeconomically diverse sample of 35 parents and 26 children (ages 5–7). Parents completed questionnaires, and hair samples were collected from parents and children. Parents reported on children's internalizing symptoms on average 2 years after the initial visit. Results demonstrated that lower parental education was associated with higher HCC for both parents and children. Effects for child HCC held even after controlling for parent HCC. Lower family income was associated with higher parent HCC, but not child HCC. This relation was nonlinear, such that the relation between HCC and income was strongest among the most disadvantaged parents. Furthermore, associations of SES with parental anxiety were significantly mediated by parental perceptions of stress and marginally mediated by parent HCC. These findings suggest that socioeconomic disadvantage is associated with greater accumulation of cortisol in hair in parents and children, and that both perceived and biological markers of stress capture important facets of the experiences that underlie socioeconomic disparities in adult anxiety.